2018
DOI: 10.1016/j.bpj.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis Model for Breast Cancer Cells Based on Signal/Noise Ratio

Abstract: Chemotaxis, a biased migration of cells under a chemical gradient, plays a significant role in diverse biological phenomena including cancer metastasis. Stromal cells release signaling proteins to induce chemotaxis, which leads to organ-specific metastasis. Epidermal growth factor (EGF) is an example of the chemical attractants, and its gradient stimulates metastasis of breast cancer cells. Hence, the interactions between EGF and breast cancer cells have long been a subject of interest for oncologists and clin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Cells close to the tumouroid start moving towards it at early timepoints but lose some of their directionality over time ( Figure 3E). It has previously been shown that chemotactic responses can be lost under excess local concentrations of ligand (Lim, Nam, and Jeon 2018), which could account for the behaviour observed here. For cells furthest from the tumouroid, directional migration commences at later timepoints ( Figure 3E).…”
Section: Long-range Diffusing Gradients Emanate From Ctls Engaging Cosupporting
confidence: 73%
See 1 more Smart Citation
“…Cells close to the tumouroid start moving towards it at early timepoints but lose some of their directionality over time ( Figure 3E). It has previously been shown that chemotactic responses can be lost under excess local concentrations of ligand (Lim, Nam, and Jeon 2018), which could account for the behaviour observed here. For cells furthest from the tumouroid, directional migration commences at later timepoints ( Figure 3E).…”
Section: Long-range Diffusing Gradients Emanate From Ctls Engaging Cosupporting
confidence: 73%
“…As additional antigen-specific CTLs are recruited and engage cognate targets, they contribute to the chemoattractive signal, thus further amplifying CTL recruitment in a positive feedback loop, which leads to swarming behaviour. Interestingly, it appears as though CTLs closest to the source of the chemotactic signal become desensitised over time and lose directional bias, which could be due to exposure to excess ligand concentrations ( Lim et al, 2018 ) or rapid internalisation of the CCR5 receptor ( Escola et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF)/EGF receptor (EGFR) signaling is a key factor in tumor growth and the development of metastasis, and is considered a target for chemotaxis in cancer therapy [ 44 , 45 , 46 , 47 ]. In order to explore the role of EGF signaling on cell migration, migration of invasive A549 cells into agarose spots was compared between EGF (recombinant human EGF)-treated and control conditions, and between IRBIT-overexpressed and IRBIT-knockdown conditions ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Models of infiltration are typically formulated under two critical assumptions. First, that energy production and consumption are non-uniform, leading to the formation of an energy gradient [51][52][53]; or second, that energy consumption is very slow compared to production, leading to an essentially infinite energetic resource [54].…”
Section: Discussionmentioning
confidence: 99%